Claims-Based Co-management in Norway's Arctic? Examining Sami Land Governance as a Case of Treaty Federalism. Issue 4 (December 2019) - Spitzer, Aaron John; Selle, Per
Abstract: Around the world, Indigenous peoples seek increased control of traditional lands. In northern Canada, such control may be afforded by claims-based co-management regimes. Such regimes are a common, and sometimes celebrated, component of treaty federalism. In Norway, Europe's only Indigenous people, the Sami, now participate in a land-management regime: the Finnmark Estate (FeFo). We explore whether FeFo is, in effect, claims-based co-management and whether Sami thus enjoy the sort of guaranteed shared rule envisioned in treaty federalism. We compare FeFo to Canadian co-management in three dimensions: novelty, independence and Indigenous influence. We conclude FeFo is indeed claims-based co-management. But FeFo falls short of the treaty-federal ideal, for reasons possibly including bureaucratic capture, fragile legitimacy, conflicting interpretations of the Sami interest and conflicting views on the merits of shared rule. Résumé: Partout dans le monde, les peuples autochtones aspirent à exercer un contrôle accru sur les terres ancestrales. Dans le Nord du Canada, ce contrôle peut être assuré par des régimes de cogestion « fondés sur les revendications ». De tels régimes sont une composante courante, et parfois célébrée, du « fédéralisme des traités ». En Norvège, le seul peuple autochtone d'Europe, les Sami participe maintenant à un régime de gestion des terres, le Finnmark Estate (FeFo). Nous examinons si le FeFo est en fait une cogestion « fondée sur les revendications » et si les Samis jouissent ainsi de la sorte de règle partagée garantie envisagée dans le « fédéralisme des traités ». Nous comparons le FeFo à la cogestion canadienne en trois dimensions : nouveauté, indépendance et influence autochtone. Nous concluons que le FeFo est en effet une co-gestion « fondée sur les revendications ». Mais, pour des raisons telles que la capture bureaucratique, une légitimité fragile, les interprétations contradictoires des intérêts des Samis et les opinions contradictoires sur les mérites d'une règle partagée, le FeFo n'atteint pas l'idéal fédéral du traité.